2001
DOI: 10.1002/ptr.733
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and antiinflammatory activities of vernonioside B2 from Vernonia condensata

Abstract: Vernonioside B2 isolated from the methanol extract of the Brazilian herb Vernonia condensata Baker was evaluated in vivo for analgesic and antiinflammatory activities. The compound reduced writhings (93.28%) and Evans blue dye diffusion (91.80%) induced by acetic acid (0.1 N) in a dose-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 9 publications
1
10
0
3
Order By: Relevance
“…It is thought that triterpenes are responsible for the antiplasmodial activity of Vernonia brasiliana (Alves et al, 1997). Lastly, some Vernonia have antipyretic, analgesic, anti-inflammatory (Valverde et al, 2001;Iwalewa et al, 2003;Mazumder et al, 2003;Cioffi et al, 2004) and cytotoxic properties (Koul et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…It is thought that triterpenes are responsible for the antiplasmodial activity of Vernonia brasiliana (Alves et al, 1997). Lastly, some Vernonia have antipyretic, analgesic, anti-inflammatory (Valverde et al, 2001;Iwalewa et al, 2003;Mazumder et al, 2003;Cioffi et al, 2004) and cytotoxic properties (Koul et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of in vitro and in vivo experiments have shown that flavonoids, tannins, triterpenoids and other secondary plant metabolites possess analgesic and anti-inflammatory properties [23–25]. Vernonioside B2, for example, identified in this plant, may contribute to the observed anti-inflammatory and antinociceptive effects of V. condensata [20]. …”
Section: Resultsmentioning
confidence: 99%
“…Analgesic, anti-inflammatory and antiulcerogenic activities of V. condensata , as well as toxicity have been investigated [18–21]. In these studies, vernonioside B2 demonstrated antinociceptive and anti-inflammatory effect [20]. Furthermore, constituents such as saponins, tannins, alkaloids, phenolic compounds and flavonoids were detected in the extracts from V. condensata [21].…”
Section: Introductionmentioning
confidence: 99%
“…(Miranda et al, 2000) e cicatrizante (Villegas et al, 1997) (Arteel et al, 2000;Abbey et al, 2008) 39 Vernonia condensata Baker. (Asteraceae) -E.Rodrigues 63 boldo inflamação folha/decocto Atividades antiinflamatória e analgésica (Frutuoso et al, 1994;Valverde et al, 2001) 40 Zingiber officinale Roscoe (Zingiberaceae) -E.Rodrigues 90 mangarataia reumatismo tubérculo/tintura Atividade antiinflamatória (Aimbire et al, 2007) 41 …”
Section: Discussionunclassified